Strategi deep learing berbasis tri-n untuk meningkatkan berpikir kritis dalam pembelajaran IPS Kelas V : pengembangan assesmen autentik terintegrasi nilai kebhinekaan - Wahyu Dwi Herawati; Heri Maria Zulfiati; Sutrisna Wibawa (Universitas Sebelas Maret, 2025)
This study aims to develop a deep learning strategy based on the Tri N approach (Niteni, Nirokke, Nambahi) integrated with authentic assessment based on diversity values to improve students' critical thinking skills in learning Social Sciences (IPS) on the material of Indonesia's geographical location in grade V of elementary school. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were elementary schools in Jogonalan District. The results of validation by three experts, namely material experts, learning and media strategy experts, and assessment and character education experts, showed that the strategies and assessments developed had a high level of validity (Aiken's V = 0.87). The results of the implementation showed a significant increase in students' critical thinking skills based on the paired sample t-test with a significance value of 0.000 (<0.05). The authentic assessment used was proven to be able to assess cognitive, affective, and diversity values holistically through projects, observations, and reflection journals. Thus, the integration of Tri N-based deep learning strategies and authentic assessments is declared valid, practical, and effective in forming contextual, critical, and character-based social studies learning.